Radiographic Assessment of Growth of Thoracic Limb Bones and Age Estimation in Fetuses of Goat (Capra hircus) - Parmar, Vimal K; Patel, Maitri J; Joshi, Nirav H; Chudasma, Milan M; Patel, Kanjibhai B; Desai, Mahendrakumar C. (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted on 103 dead goat fetuses ranging from 34 days (CR 1.55 cm) to 148 days (full term, CR 42.00 cm). The length and width of primary ossification centers of scapula, humerus, radius, ulna and large metacarpus were recorded from radiographs and statistically analyzed to assess age associated growth and to evolve age prediction formulae in the goat fetuses at death. Amongst the bones of thoracic limb the diaphyseal length of ulna showed the highest growth rate (0.94 mm/day) followed by radius, humerus, scapula and large metacarpus. The correlation coefficients between various bone measurements and fetal age were very high (r > 0.9). Among the simple linear regression equations formulated for prediction of fetal age; the length of scapula, humerus and radius gave 98 per cent predictability (R2) indicating them as reliable bone measurements for estimation of age in goat fetuses.
Keywords: Radiographic; Assessment